Participation and Yield of a Lung Cancer Screening Program in Hebei, China - Liang, Di; Shi, Jin; Li, Daojuan; Wu, Siqi; Jin, Jing; He, Yutong (Frontiers in Oncology, 2022)
Objective: Lung cancer screening has been widely conducted in the Western countries. However, population-based lung cancer screening program in Hebei in China is spare. Our study aimed to assess the participation rate and detection rate of positive nodules and lung cancer in Hebei province. Method: In total, 228 891 eligible participants aged 40–74 years were enrolled in the Cancer Screening Program in Hebei from 2013 to 2019. Total of 54 846 participants were evaluated as lung cancer high risk population by risk score system which basically followed the Harvard Risk Index and were adjusted for the characteristics of Chinese population. Then they were recommended for low dose computed tomography (LDCT) screening. And All participants were conducted annual passive follow-up, and active follow-up interval was based on radiologist’s suggestion. All participants were followed-up until December 31, 2020. The overall, group-specific participation rates were calculated, and its associated factors were analyzed by multiple logistic regression model. Participation rates and detection of positive nodules and lung cancer were reported. Results: The overall participation rate was 52.69% that 28 899 participants undertook LDCT screening as recommended. The multivariable logistic regression model demonstrated that high level of education, having disease history and occupational exposure were found to be associated with the participation in LDCT screening. The median follow-up time was 3.56 person-years. Overall, the positive lung nodules and suspected lung cancer were 12.73% and 1.46% through LDCT screening. After the native and passive follow-up, 257 lung cancer cases were diagnosed by lung cancer screening and the detection rate of lung cancer was 0.89% in screening group. And its incidence density was 298.72 per 100,000. Positive lung nodules rate and detection rate were increased with age. Conclusion: Our study identified personal and epidemiological factors could affect the participation rate. Our findings could provide the guideline of the lung cancer precisely prevention and control in the future.